2020
DOI: 10.3390/plants9091207
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Phytochemical Composition and Antioxidant Activity of Grecian Juniper (Juniperus excelsa M. Bieb) Unripe and Ripe Galbuli

Abstract: Grecian juniper (Juniperus excelsa M. Bieb.) is an evergreen tree and a rare plant found in very few locations in southern Bulgaria. The aim of this study was to evaluate the phytochemical content and antioxidant potential of J. excelsa unripe and ripe galbuli from three different locations in Bulgaria. The essential oil content ranged between 1.9% and 5.1%, while the lipid fraction yield was between 4.5% and 9.1%. The content of total chlorophyll was 185.4–273.4 μg/g dw. The total carotenoid content ranged be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Besides, catechin and ellagic acid were significantly higher in Fugu than Yijun, podophyllotoxin were significantly higher in Yijun than Fugu, and formononetin were not detected in Fugu. This is consistent with the previous studies that the sampling sites can affects phenols [14,23] …”
Section: Resultssupporting
confidence: 93%
“…Besides, catechin and ellagic acid were significantly higher in Fugu than Yijun, podophyllotoxin were significantly higher in Yijun than Fugu, and formononetin were not detected in Fugu. This is consistent with the previous studies that the sampling sites can affects phenols [14,23] …”
Section: Resultssupporting
confidence: 93%
“…Despite week natural regeneration capacity, higher number of unhealthy plants, slow growth rate, low vegetation cover, mature and over mature prevalence, the main concerns are due to human disturbances. The current study recommends initiation of long-term management and conservation programs in the area to avoid any further damage[8][9][10][11].ConclusionThe present study conducted to study cone and seed characteristics of J. excelsa concluded that the aspects (facing direction) did not play any substantial role in determining cone diameter, cone weight, seed weight, and seed characteristics of J. excelsa. A positive correlation was observed between cone diameter and cone weight, cone diameter and number of seeds per cone.…”
mentioning
confidence: 74%
“…Today, herbal medicine is in great demand throughout the world for the remedy of multiple diseases ( 12 ). The genus Juniperus is one of the chief categories of the Cupressaceae family ( 13 14 ). There are approximately 70 species of Juniperus all over the world ( 15 ).…”
Section: Introductionmentioning
confidence: 99%